Facile Aerobic Photooxidation of Alcohols Using 2-Chloroanthraquinone under Visible Light Irradiation - Shimada, Yoshiko; Hattori, Kasumi; Tada, Norihiro; Miura, Tsuyoshi; Itoh, Akichika (Synthesis, 2013)
A facile photooxidation of alcohols to obtain carboxylic acids and ketones using easily handled 2-chloroanthraquinone as an organocatalyst under visible light irradiation in an air atmosphere is reported. The reaction conditions are mild, such as an air atmosphere and ambient pressure and temperature.
Keywords: alcohols; carboxylic acids; 2-chloroanthraquinone; photooxidation; visible light